O teatro enquanto instrumento de desenvolvimento pessoal e interpessoal junto de pessoas em situação de sem-abrigo - Maria Madalena Coutinho Martins (2023)
Interventions that focus on the person as an active agent and seek to promote participation and personal development, going beyond the mere satisfaction of primary needs, are becoming increasingly common. In this sense, this research seeks to explore the value of theater as a tool for personal and interpersonal development in individuals who are homeless and/or socially vulnerable. Thus, the objectives are to analyze and understand the impact that participation in a theater workshop can have on the perception of the self, on the acquisition and/or improvement of interpersonal skills, as well as on the future prospects of the participants. Adopting a qualitative methodology, the testimonies of seven participants and five facilitators of the third workshop of the SOmOS project entitled "SOmOS Espetáculo pr'a Cidade" were collected through semi-structured interviews. The data obtained shows that, overall, taking part in a theater project had a positive impact on the way the participants perceive themselves, promoted the development of interpersonal relationships, as well as social skills such as communication and assertiveness. Sharing stories proved to be an opportunity to overcome past experiences, contributing to the recognition of individuals by others, and additionally introducing a social dimension, namely the deconstruction of stereotypes. In addition, theater gave participants a sense of purpose and personal fulfillment and promoted the development of future goals. We conclude that theater can be an important tool for promoting interpersonal skills and personal growth.